2009
DOI: 10.1007/s00404-009-1327-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of self-reported snoring and witnessed sleep apnea on gestational hypertension and fetal outcome in pregnancy

Abstract: We concluded that, although pregnant women, especially who gain excessive weight during their pregnancy, significantly snore more than nonpregnant women, this did not affect fetal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 21 publications
2
46
0
4
Order By: Relevance
“…Similarly, Ayrim and colleagues studied 200 pregnant women and 200 age-matched controls, using a questionnaire that includes questions regarding snoring, witnessed apnea, sleepiness and neck circumference. They found that although the incidence of snoring appears to increase during pregnancy, especially in women who gain excessive weight, there is no effect of fetal outcome [29]. These findings were confirmed by a study on 276 women from Korea [30].…”
Section: Maternal Sleep Disordered Breathing (Sdb) and Fetal Outcomessupporting
confidence: 75%
“…Similarly, Ayrim and colleagues studied 200 pregnant women and 200 age-matched controls, using a questionnaire that includes questions regarding snoring, witnessed apnea, sleepiness and neck circumference. They found that although the incidence of snoring appears to increase during pregnancy, especially in women who gain excessive weight, there is no effect of fetal outcome [29]. These findings were confirmed by a study on 276 women from Korea [30].…”
Section: Maternal Sleep Disordered Breathing (Sdb) and Fetal Outcomessupporting
confidence: 75%
“…1 SDB, independent of maternal BMI, is associated with an increased risk of hypertension in pregnancy, as well as maternal morbidity. 73,78,[80][81][82][83][84][85][86] In one study, preeclampsia, a hypertensive syndrome in pregnancy, was significantly more common among snorers than non-snorers (10% versus 4%, p < 0.05), as was gestational hypertension (14% versus 6%, p < 0.01). 87 This was recently corroborated in a report by O'Brien and colleagues, who found that pregnancy-onset snoring was independently associated with gestational hypertension (OR 2.36 [1.48-3.77], p < 0.001) and preeclampsia (OR 1.59 [1.06-2.37], p = 0.024) in 1,719 third-trimester pregnant women.…”
Section: Sleep Related Breathing Disorders In Pregnancymentioning
confidence: 99%
“…Sleep characteristics may change very early during pregnancy due to endocrine and anatomical modifications. As pregnancy continues, sleep duration decreases and the prevalence of insomnia, sleep-related breathing disorders, restless leg syndrome and sleepiness significantly increases [6][7][8]. Pregnancy may also aggravate an existing sleep disorder [9].…”
Section: Introductionmentioning
confidence: 96%